(untitled) (Jurnal Ilmu Komunikasi dan Bisnis, 2021)
Demonstration in a number of cities in Indonesia on October 5 to 8, 2020 as a form of rejection of the Ratification of the Omnibus Law (UU) Cipta Kerja (Ciptaker) by the government were widely reported by the mass media, especially online media. Liputan6.com and Tirto.id as one of the online news site in Indonesia also reported demonstrations conducted to reject the ratification of the Omnibus Law Act. The purpose of this research is to analyze how far Liputan6.com and Tirto.id media seek to highlight issues through the coverage of demonstrations, and how each media constructs reality and frames protests against the Omnibus Law Act in its coverage. This research used Robert M. Entman’s framing analysis to find out framing of protests against the Omnibus Law Act in Liputan6.com and Tirto.id. The results showed that Liputan6 tends to focus on the riots that occurred during the demonstrations and put aside the news about what the mass demands during demonstrations. Meanwhile Tirto.id to represent the reality of the protests against the Omnibus Law Act with more objective and balanced coverage..